Integrating Technology to Improve Teacher Preparation. Issue 2 (2nd April 2020) - Hager, Karen D.
Abstract: Many recently developed technologies have the potential to significantly improve teacher preparation programs. In this article, I describe three specific examples of integrating technology into both the coursework and field placements of a teacher preparation program. The technologies described are Nearpod for course content delivery, and GoReact and digital data forms for field placements; each was selected to address a specific program need. For each example, I describe (a) the rationale for its selection, (b) specific uses, (c) implementation/development process, and (d) piloting/evaluation of its use in courses and or field placements.